(untitled) (ModaPalavra e-periódico, 2023)
The fashion sector has been alive since the Industrial Revolution thanks to its creative and glamorous features. Fashion brands can seize determined speeches to propagate their creations. The purpose of this article is to understand how two Brazilian fashion brands appropriate and spread the message of sustainability. In the work, a qualitative approach was used through a case study in which two companies in the Brazilian fashion sector were selected and two collections were chosen for analysis. When providing information, which is defined as a difference between the concepts, it is visible that the studies of Design for Sustainability communicate institutionally and that as companies of knowledge and application of the concepts there are certain levels, but as disclosed they show incomplete. It is understood that for the occurrence of contemporary fashion it is necessary that the discourses maintain aligned to the practice.